Lehrbetriebsverbünde Integration von benachteiligten Jugendlichen in ein neues Modell der dualen Berufsausbildung in der Schweiz - Seiterle, Nicolette (Verlag Barbara Budrich, 2017)
The book shows that apprenticeship company networks in Switzerland have an increased integration potential for foreign students and weaker learners at school because they improve their chances of finding job training and prevent apprenticeship contract cancellations. The reasons for this lie in the different way in which selection and training are organised compared with individual in-company training: features specific to the network, such as rotation and shared supervision, increase learners' capabilities and act as institutional conversion factors.